The Anatolian and the Thracian horseman - Wujewski, Tomasz (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the problem of similarities and differences in depictions of the rider in the art of Anatolia and Thrace and their iconographic significance. The problem is significant for studies on the transfer of artistic and religious motifs between regions of the ancient world. The aim of the work is to determine the relationships between these representations and to explain their origin. The author applies a comparative analysis of iconographic material, including stelae, reliefs, and sarcophagi from various sites. The most important results indicate that although representations from both regions show formal similarities (e.g., the direction of the rider’s movement, the dynamics of the scene), they differ in detailed iconography and symbolic context. In Anatolia, the rider motif is associated with local deities and heroized deceased individuals, whereas in Thrace it possesses distinct, more fixed iconographic features. The absence of characteristic Thracian elements in Anatolian artifacts suggests the independence of some traditions. At the same time, similarities may result from shared cultural foundations or contacts between populations. The conclusion is that iconographic similarities are the result of both common heritage and diffusion of patterns, rather than simple borrowing.